VARIATIONS OF SERUM SIALIC ACID LEVEL IN LIVER CIRRHOSIS - Arif, Saatea; Haq, Najeeb -ul-; Hanif, Ruhila; Khan, A. Sattar; Rehman, Jamil -ur-; Mufti, Taufeeq Ahmed (Journal of Ayub Medical College Abbottabad, 2005)
Background: Cirrhosis liver claims many lives in our country. However early diagnosis carries good prognosis and prevents complications. Estimation of serum sialic acid level may be helpful in the diagnosis of liver cirrhosis and following the dynamics of the disease especially during treatment and follow up to see the prognosis. Methods: Sialic acid level of 82 confirmed liver cirrhosis patients of age between 18-60 years and admitted in Khyber Teaching Hospital Peshawar was determined and compared with 40 normal controls. The patients were studied in three groups according to the stage of the disease, i.e. the patients in early stages, in advancing stage, and those in terminal stage of liver cirrhosis. Sialic acid level was determined on HPLC (Hitachi) with D- 2500 chromatographer. Result: Significantly high levels of sialic acid were recorded in patients as compared to controls. It was normal in early stage of liver cirrhosis (667±8.06nmol/ml), markedly increased in advancing cirrhosis (952±3.29nmol/ml) (P<0.05) and very high levels were observed in terminal stage (1058±7.50nmol/ml). Conclusion: Serum Sialic acid level was high in advancing and terminal stages of disease as compared to early stage and controls that showed normal levels. Key words: N-Acetyle Neuraminic Acid (NANA), Sialic acid of glycoproteins, Cirrhosis liver.